Avaliação da detecção de antígenos NS1 e anticorpos IgM em amostras biológicas de vísceras in natura de pacientes que evoluíram para óbito por suspeita de dengue - Roque, Cássia Rodrigues (2017)
Dengue is caused by an arbovirus of the Flaviviridae family, genus Flavivirus. Cases of infection with fatal evolution began to be reported from the introduction of DENV-2 in the state of Ceará in 1994. The study of these cases is necessary to know the causes that contribute to the death and the post-mortem diagnosis of dengue can contribute. The objective of the work was to evaluate the detection of NS1 antigen and IgM antibodies for the diagnosis of dengue in biological samples of fresh viscera collected from patients who died. A total of 109 patients were included from 2013 and 2014 whose samples were sent to LACEN/CE to perform laboratory tests to confirm death due to suspected dengue and they had at least one positive result or reagent in samples of viscera in formaldehyde, blood (serum) and/or CSF in the exams IgM ELISA, NS1 ELISA, RT-PCR, and Immunohistochemistry. The mean age of the patients was 33.46 ± 21.18 (5 days to 95 years old). The IgM ELISA in the blood showed a positivity of 21.1%; in the CSF showed a positivity of 22.0%; in the viscera showed a positivity of 16.5%. Of the positive IgM samples in viscera, 75.0% were also CSF positive IgM, and 78.3% of positive IgM samples in viscera were also positive IgM in the blood. There were more NS1 positive samples in the blood than in the CSF and in viscera. CSF and blood were the samples with the highest positivity of IgM antibodies. However, IgM antibody detection was also possible in samples of fresh viscera. The immunohistochemistry technique in preserved formalin material showed a higher positivity for the detection of dengue antigens, but it was also possible to detect NS1 antigen in fresh viscera samples. The detection of IgM antibody and NS1 antigen in the fresh viscera samples helped to improve the post-mortem diagnosis of dengue and it should be considered as another approach in the diagnosis of fatal dengue.